Actual questions about using inventory rolling stock and its own one by carriages during transportation by Ukrainian railways - Belynskaia, M. H. (Science and Transport Progress, 2011)
The analysis of freight wagons in various forms of ownership was done. The issue of the actual carriage cost reimbursement by carriage component in the tariff on the basis of accounting data was investigated.